2019
DOI: 10.24875/cirue.m18000003
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of complications in dermatological surgery of melanoma and non-melanoma skin cancer in patients with multiple comorbidity and/or antiplatelet-anticoagulants. Five year experience in our Hospital

Abstract: Incidencia de complicaciones en cirugía dermatológica de cáncer de piel melanoma y no melanoma en pacientes con múltiple comorbilidad o antiagregantes-anticoagulantes. Experiencia de nuestro hospital durante 5 años

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…In contrast, several other studies found that the complication rate after treatment of KC was not different between young and elderly patients with more comorbidities, suggesting that (surgical) treatment is safe in this group, despite the higher comorbidity rate in elderly patients ( 26 , 32 , 33 ).…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…In contrast, several other studies found that the complication rate after treatment of KC was not different between young and elderly patients with more comorbidities, suggesting that (surgical) treatment is safe in this group, despite the higher comorbidity rate in elderly patients ( 26 , 32 , 33 ).…”
Section: Resultsmentioning
confidence: 65%
“…Harmonizing with these findings, a recent retrospective study including 927 KC found that patients having ≥ 4 comorbidities were significantly more likely to receive no treatment (31). In contrast, several other studies found that the complication rate after treatment of KC was not different between young and elderly patients with more comorbidities, suggesting that (surgical) treatment is safe in this group, despite the higher comorbidity rate in elderly patients (26,32,33).…”
Section: Comorbiditymentioning
confidence: 96%
“…Of the 13 articles, four were prospective observational cohort studies, one was a retrospective case-control study, and the remaining eight were retrospective observational cohort studies (Appendix S1). [15][16][17][18][19][20][21][22][23][24][25][26][27] Over 12 years, there were 10,750 patients who underwent cutaneous surgery, with 1,312 of them performed on patients prescribed a DOAC. The mean participant age ranged from 68 to 78.8 years of age, with a male predominance (49.9-81.8%).…”
Section: Resultsmentioning
confidence: 99%
“…It was not clear whether and how much skin malignancies were included [35]. Several other studies found that comorbidities did not influence (wound) complication rate after treatment of KC [32, 36, 37].…”
Section: Discussionmentioning
confidence: 99%